Psychoeducation on emotional management in students of SMA Muhammadiyah X Surakarta City - Fathia Adzka Amalia; Lintang Leonita Salsabila; Dhevi Rizky Rhomadona; Jihan Aprillia Hayyunnisa Azzahra; Rosyita Intan Khoirunnisa; Mirdian Tri Hardani; Setia Asyanti (University of Merdeka Malang, 2023)
The problem that occurred at SMA Muhammadiyah X Surakarta City based on guidance and counseling (BK) data, namely poor emotional management. Supportive observations and interviews, including mentioning nicknames of friends you don't like; mocking each other; not accepting criticism or suggestions from others; as well as unstable mood. Poor emotional management is caused by students not knowing how to manage emotions. The purpose of this psychoeducation is to provide an understanding of the importance of emotional management and training in skills to manage emotions well. The interventions used in psychoeducation are butterfly hug practices and positive affirmations, as well as breathing relaxation practices. To determine the progress of students' understanding of emotional management material, a scale of emotional management knowledge before and after psychoeducation is given. As a result, students' understanding of emotional management has improved. Students come to know there are 2 kinds of emotions (positive and negative), and relaxation is one way to manage emotions. Based on the results of psychoeducation and findings in the field, providing psychoeducation with butterfly hug practices and positive affirmations, as well as breathing relaxation practices can help improve students' knowledge and ability to manage their emotions.